Ibuprofen Degradation from Synthetic Wastewater Using Photo-Fenton Process - Abdulrazaq, Haneen Ali; Alwared, Abeer I.; Onyeaka , Helen (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The removal of Ibuprofen antibiotics (IBU) by photo-degradation UV/H2O2/Fe+2 system was investigated in a batch reactor under different initial concentrations of H2O2 (100-500) mg/L, Fe+2 (10-40) mg/L, pH (3-9) and initial concentrations of IBU (10-80) mg/L, and their relationship with the degradation efficiency were studied. The result demonstrated that the maximum elimination of IBU was 85.54% achieved at 300 mg/L of H2O2, 30 mg/L of Fe+2, pH=3, and irradiation time of 150 min, for 10 mg/L of IBU. The results have shown that the oxidation reagent H2O2 plays a very important role in IBU degradation.